2006
DOI: 10.1016/j.jtcvs.2006.01.038
|View full text |Cite
|
Sign up to set email alerts
|

Contemporary techniques and safety of cardiovascular procedures in the surgical management of renal cell carcinoma with tumor thrombus

Abstract: This large series demonstrates that aggressive treatment of renal cell carcinoma with venous thrombus provides favorable outcomes. Our 5-year survival is among the highest of recent reviews, and our perioperative morbidity and mortality rates are comparable with those of other series. Tumors that require cardiovascular procedures are associated with increased complications when compared with radical nephrectomy and thrombectomy alone. Nevertheless, this aggressive treatment approach offers encouraging patient … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
0
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(18 citation statements)
references
References 25 publications
1
16
0
1
Order By: Relevance
“…The cardiothoracic surgeon is increasingly involved [19,37] were previously excluded from their management [10,16,51]. We believe that preemptive cardiothoracic consultation is instrumental in developing such standard of care.…”
Section: Discussionmentioning
confidence: 99%
“…The cardiothoracic surgeon is increasingly involved [19,37] were previously excluded from their management [10,16,51]. We believe that preemptive cardiothoracic consultation is instrumental in developing such standard of care.…”
Section: Discussionmentioning
confidence: 99%
“…The surgical approach should not compromise the oncologic goals of the operation — it has been shown that even in the case of tumor thrombus, full surgical excision of RCC and the thrombus results in acceptable long-term survival, even when compared with patients without IVC tumor thrombus. [1314] However, the presence of BCS sharply increases the complexity of the surgery. Primarily, some patients may have a coagulopathy related to a diminished hepatic function that interferes with appropriate clotting, increasing the risk of intra- and postoperative bleeding.…”
Section: Discussionmentioning
confidence: 99%
“…According to Lubahn et al [6] approximately 50% of the patients with renal tumors involving the IVC, warrant cardiothoracic involvement. Furthermore the overall incidence of extensive IVC disease involving the right atrium according to Bissada et al [5] & Hermanek et al [7] is around 27.7%.…”
Section: Discussionmentioning
confidence: 99%
“…Generally for level III disease some institutions [9] favor cavotomy without the use of CPB [10] or with the use of venous-venous bypass [11,6]. The latter group in a large series of patients concluded that the need for invasive cardiovascular procedures increased the risk of perioperative complications.…”
Section: Discussionmentioning
confidence: 99%